Effect of Libyan Honeybee Propolis as a Natural Preservative for the Laboratory Soft Cheese : The laboratory cheese (Journal of Academic Research, 2021)
In the current study the effect of adding aqueous extract of propolis on the organoleptic properties, chemical and microbiological quality attributes of soft cheese (the laboratory soft cheese) were examined. Propolis aqueous extracts (zero, 10mℓ and 20mℓ/L) pasteurized milk were added before the manufacture of soft cheese, stored in Refrigerator at 5± 2°C for 30 days with periodical testing every 7 days. No remarkable differences were noted in organoleptic properties for both control and treated samples. In the contrary, development in acidity of control samples was more progressive than other samples were the higher propolis concentration the lower acid development. Moisture content was slightly higher in cheese with higher propolis concentration. Moreover, the most marked effect on microbial population in cheese was recorded in the coliform count. It is recommended to add propolis aqueous solution (10%) to milk in ratio of 20mℓ/liter pasteurized milk to prolong the shelf-life and improving the safety of soft cheese.